Adherence to Guidelines: Evaluation of Opioid Usage According to the Who Step Ladder Guideline in Inpatient Cancer Patients - Eko Adhi Pangarsa; Budi Setiawan; Damai Santosa; Daniel Rizky; Vina Yunarvika; Catharina Suharti (GLOBAL HEALTH SCIENCE GROUP, 2025)
WHO analgesic step-ladder is still the mainstay guideline in managing pain. However, pain in cancer patients developed from a more complex pathomechanism, hence requiring special consideration. This study aimed to compare the visual analog scale (VAS) of opioid and non-opioid analgesia in treating cancer patients and evaluate its rationality with World health organization (WHO) analgesic step-ladder.Method: A single-center, cross-sectional and analytic-descriptive study conducted in our centre. The population of this study comprised all cancer patients receiving analgesic therapy. The sampling technique used was consecutive, involving patients who met the inclusion and exclusion criteria. A total of 62 patients were included in the study as the research sample. Pain level was measured before and between 12 – 24 hours after analgesia, using VAS and divided into mild, moderate, or severe. Analgesic regimens were documented, and the daily opioid dose was presented on milligram morphine equivalent. Statistical analysis was performed to compare the variables before and after analgesia using the Wilcoxon signed-rank test, with a p-value <0.05 considered statistically significant.Result: From 62 patients, 46 subjects were included. Median milligram morphine equivalent was 20 mg (0-60). While the majority of patients experienced mild pain, 13 patients (27.7%) had moderate to severe pain. The most commonly used opioid was intravenous fentanyl, administered to 13 patients (27.7%), with a median morphine equivalent dose of 20 mg/day. Only 1 patient received opioid rationally according to WHO. Both non-opioid and opioid group had significant VAS differences before and after therapy (p = 0.014 and p <0.001). In both non-opioid and opioid groups, there were differences of VAS scores in the post-administration of analgesic, but these differences were not statistically significant (p= 0.885). Conclusion: The study concludes that, although most analgesics were not administered in accordance with the WHO step-ladder guideline, both opioid and non-opioid analgesics were effective in reducing pain in palliative cancer patients.